2019
DOI: 10.1111/chd.12744
|View full text |Cite
|
Sign up to set email alerts
|

Circulating biomarkers of left ventricular hypertrophy in pediatric coarctation of the aorta

Abstract: Objective: Patients undergoing surgical repair of aortic coarctation have a 50% risk of pathologic left ventricular remodeling (increased left ventricular mass or relative wall thickness). Endothelin 1, ST2, galectin 3, norepinephrine and B-natriuretic peptide are biomarkers that have been associated with pathologic LV change in adult populations but their predictive value following pediatric coarctation repair are not known. Hypothesis: Biomarker levels at coarctation repair will predict persistent left ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
(78 reference statements)
0
6
0
1
Order By: Relevance
“…The results presented in the study of Frank et al [ 28 ] were not promising, either. They found that galectin-3 did not predict persistent left ventricular hypertrophy nor abnormal wall thickness in children after the cardiosurgical treatment of aortic coarctation.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The results presented in the study of Frank et al [ 28 ] were not promising, either. They found that galectin-3 did not predict persistent left ventricular hypertrophy nor abnormal wall thickness in children after the cardiosurgical treatment of aortic coarctation.…”
Section: Discussionmentioning
confidence: 81%
“…On the other hand, the data regarding aortic coarctation and tetralogy of Fallot are less promising. Firstly, according to the trial of Frank et al [ 28 ], galectin-3 is not a useful biomarker for persistent left ventricular remodeling prediction during one-year follow-up in children undergoing surgical repair of aortic coarctation. Secondly, a prospective study in 16 patients with a broad range of age after surgical repair of tetralogy of Fallot [ 29 ] did not reveal any correlation between galectin-3 plasma concentrations and right heart invasive hemodynamic measurements such as right ventricular end-diastolic pressure and mean right atrial pressure in patients undergoing catheterization for pulmonary valve replacement.…”
Section: Resultsmentioning
confidence: 99%
“…Das et al ( 35 ) studied 122 CHD neonates with left obstructive lesions and found that the BNP level of the neonates was elevated, especially in neonates with critical congenital heart disease, whose BNP ranged from 553 to > 5,000 pg/ml. A significant increase in plasma BNP levels was also observed in newborns withcoarctation of aorta ( 36 ). Therefore, the BNP level is a good indicator for neonatal heart insufficiency caused by pressure load, especially for left obstructive lesions.…”
Section: Manuscript Formattingmentioning
confidence: 88%
“…Публикации последних лет выделяют эндотелин-1, ST2, галектин-3, нор эпинефрин и мозговой натрийуретический пептид в качестве биомаркеров ОРИГИНАЛЬНЫЕ СТАТЬИ § патологических изменений ЛЖ у взрослых с КоАо. Уровни биомаркеров позволяли прогнозировать стойкое ремоделирование ЛЖ через год наблюдения после коррекции коарктации, но окончательная их прогностическая ценность неизвестна [25].…”
Section: Discussionunclassified